IMPLEMENTATION SUSPENSION OF STATE ADMINISTRATIVE DECISION BY THE STATE ADMINISTRATIVE COURT - Asmuni Asmuni (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
AbstractBased on the principle of presumption Rechmatiq / Praesumptio iustae causa thatthe decision of the State Administrative (KTUN) should be considered legal until there is a court decision stating the contrary, it is in order that the task of the government is viable in particular to provide protection, public services and welfare for people, but as a counterweight to provide legal protection to the interests of the plaintiff, the judge may issue a suspension in the implementation. Stipulation is a legal product that was originated from the requests (no dispute) but in this case there is a dispute over the State Administration, but the judge may issue a stipulation of the suspension.Keywords: Implementation Suspension of State Administrative Decisions lead tolaw situation/condition (rechtstoestand) back to the former state or position (restitutio in integrum) prior to the decision of the State Administrative being disputed.